A dialogue manager for accessing databases - Abreu, Salvador (2012)
We present a logic programming based dialogue system that enables the access in natural language to the heterogeneous external relational databases of the Évora University. The proposed system has the capability of inferring user attitudes and uses ISCO in order to view the University relational databases as a part of a declarative/deductive object-oriented (with inheritance) database allowing the mapping of relational tables to classes – which may be used as logic (Prolog) predicates.